A dual‐phase‐conducted type bearingless switched reluctance flywheel motor with hybrid outer rotor. Issue 9 (23rd February 2021) - Zhou, Yunhong; Jiang, Jiahao; Sun, Yukun; Zhu, Zhiying
Abstract: A novel dual‐phase‐conducted type bearingless switched reluctance flywheel motor is proposed, which has a hybrid outer rotor comprising circular segment and scalloped lamination segment, and only one set of winding is placed on each stator pole. In order to drive the flywheel to accelerate or slow down, two phases of windings in this motor conduct simultaneously. One phase provides radial suspension force, and the other phase provides electromagnetic torque. There exits satisfying decoupling between torque and suspension force. With the circular segment of the rotor, the continuity and stability of radial force can be enhanced. Finite element analysis results confirm the feasibility of the theoretical scheme.